2019
DOI: 10.3390/rs11202394
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Accurate Monitoring of Intertidal Oyster Reef Habitat Using Unoccupied Aircraft Systems and Structure from Motion

Abstract: Oysters support an economically important fishery in many locations in the United States and provide benefits to the surrounding environment by filtering water, providing habitat for fish, and stabilizing shorelines. Changes in oyster reef health reflect variations in factors such as recreational and commercial harvests, predation, disease, storms, and broader anthropogenic influences, such as climate change. Consistent measurements of reef area and morphology can help effectively monitor oyster habitat across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Our oyster density results over time and space also show declines in oyster counts, with the largest declines occurring in inshore areas, which may be becoming more like offshore and nearshore regions based on counts ( Figure 6). What is not known is whether these inshore losses are offset by the formation of new reefs elsewhere, although this could possibly be assessed through satellite, drone-based, or other surveys (Grizzle et al 2018;Windle et al 2019). Seavey et al (2011) reported the inland colonization of a salt marsh by oysters in inshore areas of Suwannee Sound, but those increases did not offset net losses experienced in nearshore and offshore reefs.…”
Section: Trends In Oyster Populations In the Gulf Of Mexicomentioning
confidence: 99%
“…Our oyster density results over time and space also show declines in oyster counts, with the largest declines occurring in inshore areas, which may be becoming more like offshore and nearshore regions based on counts ( Figure 6). What is not known is whether these inshore losses are offset by the formation of new reefs elsewhere, although this could possibly be assessed through satellite, drone-based, or other surveys (Grizzle et al 2018;Windle et al 2019). Seavey et al (2011) reported the inland colonization of a salt marsh by oysters in inshore areas of Suwannee Sound, but those increases did not offset net losses experienced in nearshore and offshore reefs.…”
Section: Trends In Oyster Populations In the Gulf Of Mexicomentioning
confidence: 99%
“…26 [32]. In pre-processing, the ground control targets were located in the imagery and associated with their respective coordinates to enhance the spatial accuracy of outputs [19]. Pix4D Mapper was used to estimate the position, angular orientation, and camera calibration parameters of the images, and to subsequently generate an orthomosaic and DSM.…”
Section: Image Processing and Geographic Object-based Image Analysismentioning
confidence: 99%
“…The NOAA Oyster Restoration Workgroup suggests monitoring metrics such as population structure, recruitment, disease, and vertical relief of oyster reefs to provide a more complete outlook on the health of reefs and populations [7,12]. UASs can provide informative data on these metrics, the most direct application being vertical relief and morphology, which has been conducted successfully for eastern oyster reefs in other areas such as off the coast of North Carolina, USA [19].…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations